GTSE1: a novel TEAD4-E2F1 target gene involved in cell protrusions formation in triple-negative breast cancer cell models - Stelitano, Debora (2017)
Dissemination of cancer cells from the primary tumors to distant organs represents the main cause of death in cancer patients. GTSE1 over-expression has been reported as a potential marker for metastasis in various types of malignancies including breast cancer where GTSE1 expression levels correlate with tumor grade, enhanced invasive potential and negative prognosis. Given the tight correlation between GTSE1 deregulation and bad clinical outcome the aim of this work was to clarify how GTSE1 is regulated in TNBC and the molecular mechanism underlying GTSE1-dependent cell movement. Here, we identified GTSE1 as a novel direct TEAD4 and E2F1 transcription factors target gene highlighting a role for YAP and TAZ co-activators in GTSE1 transcriptional regulation. Frequently deregulated in cancers, TEAD4 and the co-activators YAP and TAZ have been reported to promote tumorigenesis, invasion and metastasis in breast cancer. Here, we demonstrated that the effect of TEAD transcription factor on cell migration and invasion is GTSE1-dependent. Moreover, we found that TEAD controls cell protrusions formation, required for cell migration, through GTSE1 protein unveiling a relevant effector role for GTSE1 in the TEAD-dependent cellular functions.